Developing character education in Islamic primary schools through a teoanthropoecocentric paradigm - Moh. Asy’ari; Badruddin Tohir; Ahmad Faizal Dzat; Riayatul Husnan (EDUCARE Journal of Primary Education, 2025)
This study highlights the fragmented nature of character education in Madrasah Ibtidaiyah, which tends to emphasize normative moral–religious instruction while neglecting anthropological and ecological dimensions. The absence of an integrative paradigm weakens holistic character formation, social responsibility, and environmental awareness, necessitating a theoanthropoecocentric approach in educational practice. The study aims to examine the implementation of the theoanthropocentric paradigm in character education at Madrasah Ibtidaiyah through the integration of divine, human, and environmental values in learning processes and daily educational practices. Employing a literature review method, this research analyzes character education grounded in the theoanthropocentric paradigm through rigorous source selection and conceptual synthesis to strengthen the theoretical foundation of holistic character education integrating theocentric, anthropocentric, and ecocentric values. The findings indicate that the theoanthropoecocentric paradigm effectively fosters holistic character development among Madrasah Ibtidaiyah students by integrating divine, human, and environmental values. Character education extends beyond normative moral instruction toward lived religious practice, ethical social relations, and ecological responsibility, with effectiveness contingent upon implementation consistency, institutional support, and school culture. The implications underscore the need to strengthen policies, curricula, and school culture that consistently integrate divine, human, and ecological values, alongside enhancing teachers’ roles as role models in promoting sustainable and holistic character education in Madrasah Ibtidaiyah.